"Maybe That Concept Is Still with Us": Adolescents' Racialized and Classed Perceptions of Teachers' Expectations. (2nd January 2017) - Andrews, Dorinda J. Carter; Gutwein, Melissa
Abstract : Teacher expectations for student behavior and academic performance have a lasting effect on student academic achievement—not only in the immediate school year, but also many years later. Yet, we know very little about how students interpret and understand teachers' expectations for them. This article expands the literature on teachers' expectations for students by drawing on student voice to examine how middle and high school students describe and experience the expectations that teachers have for them, and the implications of these expectations for developing positive student–teacher relationships. Findings indicate that traditionally minoritized and traditionally privileged youth harbor racialized and classed perceptions of teachers' expectations. I feel like it's all around us too, like everything we hear kinda everything we learn about; it's kinda like minorities are oppressed. Like you learn about, a lot about, like, civil rights and all that; like you always kinda hear that, like, Blacks, minorities, all of them were kinda oppressed and that Whites were dominant at one point. So I mean it's not like it's the same; it's not completely different now, but maybe that concept is still with us. (Latina/o high school student)